2006
DOI: 10.1213/01.ane.0000216036.95705.c2
|View full text |Cite
|
Sign up to set email alerts
|

Development of Acute Opioid Tolerance During Infusion of Remifentanil for Pediatric Scoliosis Surgery

Abstract: We tested the hypothesis that continuous intraopera-tive infusion of remifentanil is associated with the development of clinically relevant acute opioid tolerance in adolescents undergoing scoliosis surgery. Thirty adolescents were randomly assigned to receive an intra-operative analgesic regimen consisting of continuous remifentanil infusion or intermittent morphine alone. Postoperative analgesic consumption was assessed with a patient-controlled analgesia device that was used to self-administer morphine. Cum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(92 citation statements)
references
References 25 publications
4
87
1
Order By: Relevance
“…The sample size estimation was based on a study from this institution demonstrating that the initial 24-hr morphine consumption after surgery for idiopathic scoliosis was 1.65 mg.kg -1 + 0.41 mg.kgq. 3 To demonstrate a 25% difference in 24-hr morphine consumption (0.41 mg.kg-~), we estimated that 18 patients per group were required for a two-tailed (x of 0.05 and a tg of 0.2 (power = 80%). Forty patients were recruited to accommodate any potential protocol violations or dropouts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample size estimation was based on a study from this institution demonstrating that the initial 24-hr morphine consumption after surgery for idiopathic scoliosis was 1.65 mg.kg -1 + 0.41 mg.kgq. 3 To demonstrate a 25% difference in 24-hr morphine consumption (0.41 mg.kg-~), we estimated that 18 patients per group were required for a two-tailed (x of 0.05 and a tg of 0.2 (power = 80%). Forty patients were recruited to accommodate any potential protocol violations or dropouts.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative infusion of remifentanil was associated with the development of hyperalgesia manifesting clinically as an increase in postoperative morphine consumption. 3,4 The increase in postoperative morphine consumption was variable, ranging fi:om 30% to 100% for comparable durations of remifentanil infusion. 3,4 One explanation offered for the observed differences in postoperative opioid consumption between these studies was that morphine administered at induction of anesthesia may have had a preemptive analgesic effect, thereby attenuating the development of remifentanil-induced acute opioid tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative PCA morphine requirements in children with sickle-cell disease were almost double those of nonsickle children (Crawford, Galton et al, 2006 Level III-3). Intraoperative remifentanil was associated with an increase in PCA morphine requirement in the 24 hours following scoliosis surgery (Crawford, Hickey et al, 2006 Level II), possibly due to acute opioid-induced hyperalgesia.…”
Section: Efficacymentioning
confidence: 99%
“…Moreover, some authors have reported that a factor involved in the hyperalgesia is the short duration of action of opioids, such as remifentanil [7][8][9][10] . The main mechanism of hyperalgesia induced by opioids is the activation of N-methyl-D-aspartate (NMDA) receptors [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%